Gutiérrez et al. (2022), Turismo Sostenible: Reactivación Económica en Tiempos de COVID-19. Huanta -Ayacucho: Fondo Editorial UNAH. 162 pp. - Cristobal-Lobaton, Idelia Mirta (2023)
The present review of the book whose authors Gutiérrez, E., Pariona, B. Ccama, F.; González, C. Moscoso, K, Trujillo and J; Castro, W., subject of analysis, comprises 162 pages, VII chapters, as established in the introduction of the book (p.10), Moscoso, remarks the approaches of the authors as problems of the social environment, need for professionals in the administration of lodging, good practices of sustainable tourism and the need for intervention in cultural and religious tourism.